2013
DOI: 10.1152/ajpcell.00364.2012
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II regulates ACE and ACE2 in neurons through p38 mitogen-activated protein kinase and extracellular signal-regulated kinase 1/2 signaling

Abstract: Brain ANG II plays an important role in modulating sympathetic function and homeostasis. The generation and degradation of ANG II are carried out, to a large extent, through the angiotensin-converting enzyme (ACE) and ACE2, respectively. In disease states, such as hypertension and chronic heart failure, central expression of ACE is upregulated and ACE2 is decreased in central sympathoregulatory neurons. In this study, we determined the expression of ACE and ACE2 in response to ANG II in a neuronal cell culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 42 publications
5
52
0
Order By: Relevance
“…It has been reported that Ang II levels are increased in the stroke cortex one day after stroke 23 , and others have shown Ang II to upregulate ACE, AT1R, and TACE, and decrease ACE2 expression 24, 25 , which might account for some of the changes that we have observed one day post-stroke (Fig. 1C, Fig.…”
Section: Discussionsupporting
confidence: 58%
“…It has been reported that Ang II levels are increased in the stroke cortex one day after stroke 23 , and others have shown Ang II to upregulate ACE, AT1R, and TACE, and decrease ACE2 expression 24, 25 , which might account for some of the changes that we have observed one day post-stroke (Fig. 1C, Fig.…”
Section: Discussionsupporting
confidence: 58%
“…AT1R/p38 MAPK, an important signalling pathway, is involved in pancreatic fibrosis, renal tubulointerstitial fibrosis, and peritoneal fibrosis. Moreover, previous studies have reported that activation of the AT1R/p38 MAPK pathway induces an imbalance in the ACE/ACE2 ratio in HK-2 cells and neurons78.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have suggested the involvement of the AT1R/p38 MAPK pathway in pancreatic fibrosis5, renal tubulointerstitial fibrosis6, and peritoneal fibrosis7. Importantly, the AT1R/p38 MAPK pathway also affects the RAS by modulation of the ACE/ACE2 ratio8. These findings indicate a regulatory mechanism that operates between the AT1R/p38 MAPK pathway and RAS in the development of fibrotic disease.…”
mentioning
confidence: 99%
“…38 Also, Akt phosphorylation is an important phenomenon in the signal transduction pathway activated by growth factors, including Ang-II. 38 In vitro studies using cultured rat vascular smooth muscle cells 8 or neuronal cells, 36 showed that MAP kinase and ERK1/2 pathways are involved in AT 1 R mediated changes in ACE2 expression. In the present in vivo study, we show that ACE2 overexpression prevented the DOCA-salt induced phosphorylation of both Akt and ERK1/2 in the PVN suggesting that the beneficial effects of ACE2 overexpression on hypertension are mediated by Akt and ERK1/2 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%